S143 Evidence that Type I interferon drives pulmonary arterial hypertension. (14th November 2013) - George, PM; Oliver, E; Schreiber, BE; Holmes, AM; Southwood, M; Wort, SJ; Bartlett, N; Dorfmuller, P; Morrell, NW; Coghlan, G; Humbert, M; Zhao, L; et al.
Abstract : Rationale: There is increasing evidence of a link between interferon (IFN) and pulmonary arterial hypertension (PAH). Conditions such as HIV and Systemic sclerosis (SSc) where endogenous IFN levels are chronically elevated are strongly associated with PAH. Furthermore, therapeutic use of type I IFN is now known to cause PAH and increase the systemic release of endothelin (ET)-1 in some patients. The link between IFN therapy and PAH was formally recognised at the 5-yearly World Symposium on Pulmonary Hypertension (Nice, Feb 2013). Our group has identified the mitogen ET-1 and the archetypal interferon stimulated gene - interferon gamma inducible protein 10 (IP10) as candidate mediators for IFN induced PAH. Using a comprehensive approach incorporating human pulmonary vascular cells in vitro, genetically modified mice in vivo and clinical samples with patient data we sought to explore the role of type I IFN in PAH. Methods: Primary cells were cultured and responses measured using standard approaches. Serum cytokine and ET-1 levels were measured by ELISA. The role of type I IFN in PAH in vivo was determined using type I IFN receptor knock out (IFNAR1 -/- ) mice and the chronic hypoxia model of PAH. Results: Human pulmonary artery smooth muscle cells expressed the type I IFN receptor and released ET-1 (Fig. 1a ) and IP10 in response to IFNα. In patients with SSc associated PAH, serum IP10 and ET-1 levels were raised and correlated positively together (Fig. 1b ). In addition IP10 correlated strongly with pulmonary haemodynamics and 6 minute walk distance (Fig. 1b ). Finally, IFN was found to mediate PAH in vivo since mice lacking a functioning type I IFN receptor were protected from hypoxia induced PAH (Fig. 1c ). Discussion and Conclusions: These novel data reveal a clear pathological role for type I IFN in PAH and provide crucial insight into the mechanisms underpinning pulmonary vascular toxicity associated with type I IFN therapies. Furthermore, endogenous IFN elevated in autoimmune disease or viral infection, are now implicated in PAH. We conclude that type I IFN, via an action of IFNAR1 and potentially through ET-1 and IP10, mediates PAH and may represent a novel therapeutic target.